2010
DOI: 10.1037/a0018451
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and indicators of adjustment during rehabilitation from a spinal cord injury.

Abstract: Future studies that focus on developing interventions and examine the factors that predict resilience could help build resilience, which in turn may improve rehabilitation outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
160
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(180 citation statements)
references
References 56 publications
14
160
2
4
Order By: Relevance
“…However, evidence is weak and based on single studies. High spirituality and PIL were associated with higher life satisfaction and well-being, 63,84,85 better mental health 84 and adjustment 86 and, as shown in longitudinal research, reduced mortality. 87 Spirituality was not associated with functional independence.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…However, evidence is weak and based on single studies. High spirituality and PIL were associated with higher life satisfaction and well-being, 63,84,85 better mental health 84 and adjustment 86 and, as shown in longitudinal research, reduced mortality. 87 Spirituality was not associated with functional independence.…”
Section: Resultsmentioning
confidence: 65%
“…87 Spirituality was not associated with functional independence. 84 Both, cross-sectional and longitudinal studies indicated changes in spirituality after SCI, 53,84 and similar spirituality levels to persons with other health conditions. 88,89 One large study reported significant but low correlations of PIL with health locus of control and various personality attributes.…”
Section: Resultsmentioning
confidence: 96%
“…8 Despite its relative importance in the psychological adjustment process, the process of resilience post-SCI has been relatively understudied. 6,8 Furthermore, there are conflicting findings relating to the cognitive, behavioural and injury-specific variables that may offer protection and enhance the adjustment process. 8 For example, it is argued that the permanent and physical constraints associated with SCI contribute to poor self-efficacy with regard to pain management.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although researchers have made important contributions towards identifying negative outcomes for individuals with SCI using the deficit-based paradigm, 2 it has not assisted researchers in finding ways to prevent psychological problems from developing. 2,6,7 In comparison, the strength-based model of mental health, which evolved from the positive psychology movement, focuses on the variables that buffer against mental illness. 2,8 The strength-based model has also introduced concepts such as 'resilience' in the rehabilitation literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation